Pengaruh Promosi dan Citra Destinasi Terhadap Niat Berkunjung Ke Destinasi Wisata Pulau Menjangan Bali - I Putu Edi Purna Ariawan Edi Purna; Komang Endrawan Sumadi Putra (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This study aims to analyze the influence of promotion and destination image on tourists’ intention to visit Menjangan Island, Bali. Using a causal quantitative approach, data were collected through questionnaires from 100 tourists. Promotion and destination image were treated as independent variables, while visiting intention was the dependent variable. Data analysis was conducted using multiple linear regression. The results show that both promotion and destination image have a positive and significant effect on visiting intention, both individually and simultaneously. This indicates that effective promotional activities and a strong, positive image of the destination can increase tourists’ interest in visiting. Therefore, destination managers are encouraged to enhance creative and sustainable promotion strategies and maintain a positive destination image through good environmental management, improved facilities, and quality tourism services.